PENGELOLAAN ASUHAN KEPERAWATAN BERBASIS EDUKASI PERAWATAN LUKA DAN NUTRISI PADA PASIEN POST OPERATIVE DENGAN KOMPLIKASI BURST ABDOMEN DAN HIPOALBUMINEMIA: CASE REPORT - Putri, Angeli Soradin; Yudianto, Kurniawan; Nurhakim, Furkon (SINERGI : Jurnal Riset Ilmiah, 2026)
Postoperative wounds are at high risk for complications such as infection, wound dehiscence, and sepsis, particularly in patients with hypoalbuminemia that impairs tissue regeneration. This case report aims to evaluate the effectiveness of nursing care management based on education about wound care and nutrition in improving the knowledge of patients and families. Method: A descriptive case report approach was conducted on Mrs. S (32 years old) diagnosed with burst abdomen and hypoalbuminemia after open cholecystectomy in the Medical-Surgical Inpatient Unit of Hospital X. The intervention consisted of educational sessions using leaflet and video media based on Evidence-Based Practice (EBP), covering aseptic principles, wound care steps, signs of infection, and the importance of high-calorie high-protein (HCHP) nutrition. Evaluation was performed using pre-test and post-test assessments. Results: The patient’s knowledge score increased from 40 (pre-test) to 100 (post-test), while the family’s knowledge improved from 40 to 80. Analysis using the 3M approach (Man, Method, Material) indicated that educational effectiveness was supported by active involvement of nurses and family, interactive learning methods, and accessible educational media. Conclusion: Implementation of 3M-based nursing management through combined leaflet and video education proved effective in enhancing the knowledge, skills, and preparedness of patients and families in performing independent wound care at home